Switching between phosphorescence and fluorescence controlled by chiral self-assembly - Liu, Guofeng (2019)
Helical self‐assembly plays a unique role in regulating the localized excitations of π functional systems, which can also bring highly multi‐scale orders, and show a special effect to tune the energy of electronics, vibration, and rotation of molecules. Due to controllable and dynamic property of chiral self‐assembly, highly ordered and helical assemblies can be obtained to exhibit amplification effect and fascinating photophysical properties in photoluminescence. However, an effective control of singlet‐triplet emissive switching in a unimolecular platform remains a great challenge. Recently, switchable singlet‐triplet emission induced by helical self‐assembly in a unimolecular platform has been developed. By taking advantage of the helical self‐assembly driven by multiple intermolecular hydrogen bonding and strong π‐π stacking interactions, reversible switching between fluorescence and phosphorescence could be efficiently achieved both in N,N‐dimethylformamide/H2O solution and the solid state. The results will inspire the design of other intelligent luminescent materials through chiral self‐assembly and be valuable for interdisciplinary development of supramolecular self‐assembly and related materials science.